Focusing on persistent hypoxemia during VV-ECMO secondary to traumatic tricuspid valve injury: a case report - Yunpeng Zhao; Jing Liu; Kun Chen (Frontiers in Medicine, 2026)
Background Veno-venous extracorporeal membrane oxygenation (VV-ECMO) is a life-saving salvage therapy for treating severe respiratory failure. We present a case of trauma-related hypoxemia with severe tricuspid chordae tendinae rupture managed with VV-ECMO. Case presentation We report the successful use of VV-ECMO in a 29-year-old patient with severe acute respiratory distress syndrome (ARDS). Refractory hypoxemia persisted despite maximal conventional therapy during the course of treatment at the outside hospital. Under VV-ECMO support, the patient’s oxygen saturation improved, allowing for the down-titration of ventilator parameters. However, when an attempt was made to reduce the ECMO settings, the patient’s oxygen saturation decreased. Transesophageal echocardiography (TEE) revealed a traumatic rupture of the tricuspid chordae tendineae, which was identified as the underlying etiology of the patient’s severe ARDS. Following surgical repair and subsequent improvement in oxygenation, the patient was successfully decannulated from VV-ECMO. Post-decannulation, the patient developed a high fever, later confirmed as Burkholderia cepacia infective endocarditis, which responded well to targeted antimicrobial therapy. Conclusion VV-ECMO should be considered a viable supportive therapy for patients with trauma-induced ARDS. However, if acute hypoxemia persists despite conventional interventions during VV-ECMO support, immediate differential diagnosis is warranted. Notably, bedside echocardiography serves as a critical tool for identifying underlying cardiac etiologies of refractory hypoxemia.